2019
DOI: 10.1038/s41467-019-13299-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of cyclone activity in snow accumulation on Arctic sea ice

Abstract: Identifying the mechanisms controlling the timing and magnitude of snow accumulation on sea ice is crucial for understanding snow’s net effect on the surface energy budget and sea-ice mass balance. Here, we analyze the role of cyclone activity on the seasonal buildup of snow on Arctic sea ice using model, satellite, and in situ data over 1979–2016. On average, 44% of the variability in monthly snow accumulation was controlled by cyclone snowfall and 29% by sea-ice freeze-up. However, there were strong spatio-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 56 publications
3
37
0
Order By: Relevance
“…The correspondence in the h Δf , h ERA ‐ I , and h ERA5 composites as well as the IS‐2 and CS‐2 freeboard composites suggests that this regional increase in snow depth is due to enhanced snow accumulation. To investigate snowfall conditions for this season, we examined the number, strength, and snowfall of cyclones, which is the primary source of snow accumulation in the Chukchi region (Webster et al, 2019). Using the Melbourne University Cyclone Tracker (Simmonds et al, 2008), we found heightened cyclone frequency, intensity, and cyclone‐associated snowfall in the western Chukchi region for the 2018–2019 winter period relative to the 1979–2019 climatological mean (Figure 5).…”
Section: Snow Depth Estimatesmentioning
confidence: 99%
“…The correspondence in the h Δf , h ERA ‐ I , and h ERA5 composites as well as the IS‐2 and CS‐2 freeboard composites suggests that this regional increase in snow depth is due to enhanced snow accumulation. To investigate snowfall conditions for this season, we examined the number, strength, and snowfall of cyclones, which is the primary source of snow accumulation in the Chukchi region (Webster et al, 2019). Using the Melbourne University Cyclone Tracker (Simmonds et al, 2008), we found heightened cyclone frequency, intensity, and cyclone‐associated snowfall in the western Chukchi region for the 2018–2019 winter period relative to the 1979–2019 climatological mean (Figure 5).…”
Section: Snow Depth Estimatesmentioning
confidence: 99%
“…Precipitation associated with cyclone passage over the Arctic Ocean can be in the form of snow or rain. Cyclones are the primary source of snow on sea ice in the Arctic (Webster and others, 2019), though the fraction of precipitation falling as rain is increasing and expected to dominate in the future (Screen and Simmonds, 2012; Bintanja and Andry, 2017). Rainfall decreases the surface albedo, resulting in greater energy absorption, while fresh snowfall increases surface albedo (Screen and others, 2011) and slows melt in summer.…”
Section: Introductionmentioning
confidence: 99%
“…Sea ice flooding is dependent on whether the sea ice is permeable or there exist potential pathways such as cracks [32], [36]. In the Arctic, flooding is likely to occur frequently in the Atlantic sector, which experiences more precipitation and thicker snow on thinner sea ice [36], [37] compared to other regions.…”
Section: Introductionmentioning
confidence: 99%